SOSIALISASI TENTANG PHBS CARA MENGGOSOK GIGI YANG BAIK DAN BENAR SEJAK DINI - Amalia Gobel; Sucia Pratiwi Tampoy (Journal of Hulonthalo Service Society (JHSS), 2025)
Health is one of the important factors in efforts to develop Human Resources (HR), including education. Therefore, it becomes natural for health insurance. Healthy living behavior is one of the important efforts made in creating healthy environmental conditions, especially elementary school children who are still in the growth and development stage. Toothbrush is one of the most effective oral physiotherapy tools. It is widely used for cleaning teeth and mouth. The method used in providing assistance to the community in Salepae Village is the method of lectures, discussions and practices accompanied by games so that the community participating in the community service activities that are held do not feel bored when studying theory. The results of the implementation of community service activities that have been carried out for two months from identifying problems to studying theories have had a positive impact on the community, this can be seen by changing the mindset of the community, and increasing public awareness about the benefits of mosque financial priorities.